Hedged Language and Partisan Media Influence Belief in Science Claims. Issue 2 (April 2020) - Butterfuss, Reese; Aubele, Joseph; Kendeou, Panayiota
Sources of scientific information vary in partisanship and epistemic stance toward science. The current study examined how hedged language (certain vs. tentative) and partisanship of sources (liberal vs. conservative vs. scientific sources) interacted with participants' epistemic beliefs and political ideology to influence belief in science-related claims and trust in sources. Findings showed that "hedged" language influenced belief in information for individuals with certain epistemic profiles. Participants with higher faith in intuition demonstrated lower belief in claims from scientific sources. Additionally, individuals with a higher conviction that "truth" is political demonstrated lower belief when liberal sources used certain language.